Sosialisasi dan Pembuatan Hidroponik untuk Mendukung Program Penghijauan Lingkungan di Kelurahan Plosokerep, Kecamatan Sananwetan, Kota Blitar - Aldien Ramadhan; Bagus Wahyu Tri Pambudi; Arifiana Nur Hanifah; Dewi Deniaty Sholihah; Nanik Hariyana (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Environmental pollution has become an old problem that often has not been found a solution, one of which is in Plosokerep Village, Sananwetan District, Blitar City. Environmental pollution can cause disruption of the habitat of living things which in turn will affect the population of these living things. Efforts that can be made to reduce environmental pollution, one of which is the reforestation program. One of them can be done with hydroponics. Hydroponics is a farming strategy without using soil, but using water to fulfill plant needs. The polluted environment caused by human activities can make nature unable to return to its unique state. The implementation method used by the KKN 141 UPN "Veteran" East Java Group in this community service is the method of socialization and assistance in making hydroponics which is carried out especially for members of the Mekar Asri Women Farmer Group, Plosokerep Village. The chosen hydroponics is in the form of verticulture, adjusting to the environment around Plosokerep Village which has limited land. The goal to be achieved from this activity is that residents of Plosokerep Village, Sananwetan District, Blitar City cam gain basic knowledge of hydroponic cultivation and have the ability to make hydroponics and maintain it, so that they can support environmental reforestation programs, increase economic income, and family food security. Keywords: Pollution, Environment, Greening Program, Hydroponics Verticulture